Cell death induced by ozone and various non-thermal plasmas: therapeutic perspectives and limitations - Lunov, Oleg; Zablotskii, Vitalii; Churpita, Olexander; Chánová, Eliška; Syková, Eva; Dejneka, Alexandr; Kubinová, Sárka (Scientific reports, 2014)
Non-thermal plasma has been recognized as a promising tool across a vast variety of biomedical applications, with the potential to create novel therapeutic methods. However, the understanding of the molecular mechanisms behind non-thermal plasma cellular effects remains a significant challenge. In this study, we show how two types of different non-thermal plasmas induce cell death in mammalian cell cultures via the formation of multiple intracellular reactive oxygen/nitrogen species. Our results showed a discrepancy in the superoxide accumulation and lysosomal activity in response to air and helium plasma, suggesting that triggered signalling cascades might be grossly different between different plasmas. In addition, the effects of ozone, a considerable component of non-thermal plasma, have been simultaneously evaluated and have revealed much faster and higher cytotoxic effects. Our findings offer novel insight into plasma-induced cellular responses, and provide a basis for better controlled biomedical applications.
Keywords: buněčná smrt; vzduch; reaktivní formy dusíku; Acetylcysteine; nádorové buněčné linie; signální transdukce; Lysosomes; Rats; Antioxidants; Plasma Gases; reaktivní formy kyslíku; Annexin A5; Neuroglia; Signal Transduction; Reactive Nitrogen Species; neuroglie; Mice; Cell Line, Tumor; buňky 3T3; membránový potenciál mitochondrií; acetylcystein; krysa rodu Rattus; plazmové plyny; antioxidancia; Cell Death; Reactive Oxygen Species; ozon; 3T3 Cells; zvířata; helium; Ozone; viabilita buněk; Cell Survival; annexin A5; lyzozomy; myši; Membrane Potential, Mitochondrial; Air; Helium; Animals